1999
DOI: 10.1017/s0950268898001848
|View full text |Cite
|
Sign up to set email alerts
|

Is group C meningococcal disease increasing in Europe? A report of surveillance of meningococcal infection in Europe 1993–6

Abstract: A surveillance system to assess the impact and changing epidemiology of invasive meningococcal disease in Europe was set up in 1987. Since about 1991, contributors from national reference laboratories, national communicable disease surveillance centres and institutes of public health in 35 European countries provided information on all reported cases of meningococcal disease in their country. We describe some trends observed over the period 1993-6. The main findings were: the overall incidence of meningococcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 5 publications
5
65
1
1
Order By: Relevance
“…With respect to serogroup C, an increasing predominance was observed in late 90s and early 2000s also in other European countries. [11][12][13][14] As also observed by Mooney et al 14 , the reversal of the increasing trend of serogroup C related IMD was simultaneous with the timing of MCC introduction and, therefore, likely attributable to it. The impact of MCC was investigated in many other European and Italian regional studies [14][15][16][17][18][19][20][21][22][23][24][25] which showed an important decrease in N. meningitidis C related IMD and a vaccine effectiveness as high as 100% depending on the age group and on the time elapsed from vaccination.…”
Section: Discussionsupporting
confidence: 56%
“…With respect to serogroup C, an increasing predominance was observed in late 90s and early 2000s also in other European countries. [11][12][13][14] As also observed by Mooney et al 14 , the reversal of the increasing trend of serogroup C related IMD was simultaneous with the timing of MCC introduction and, therefore, likely attributable to it. The impact of MCC was investigated in many other European and Italian regional studies [14][15][16][17][18][19][20][21][22][23][24][25] which showed an important decrease in N. meningitidis C related IMD and a vaccine effectiveness as high as 100% depending on the age group and on the time elapsed from vaccination.…”
Section: Discussionsupporting
confidence: 56%
“…This setting resembled the situation in Norway, where B : 15 : P1.7,16 (belonging to the ET-5 complex) has been predominant for more than two decades. In contrast to other European countries, in which increases in IR have been related to C : 2a : P1.2,5 (Krïzová et al, 1997;Kremastinou et al, 1999;Connolly & Noah, 1999), the occurrence of this phenotype actually decreased in North Jutland County during 1990-99.…”
Section: Resultsmentioning
confidence: 74%
“…There is an urgent need for a vaccine against serogroup B meningococci, as this serogroup is now the most common cause of infection in many countries (Connolly & Noah, 1999). Since the introduction of meningococcal serogroup C conjugate vaccines in the UK, there has been a decrease in the incidence of serogroup C disease, and serogroup B is therefore even more predominant.…”
Section: Discussionmentioning
confidence: 99%
“…Such systems can often provide rapid results when cultures are available and can be useful for public health management Feavers et al, 1999). The provision of these data also provides long-term surveillance data that can be used for informing vaccine policy.There is an urgent need for a vaccine against serogroup B meningococci, as this serogroup is now the most common cause of infection in many countries (Connolly & Noah, 1999). Since the introduction of meningococcal serogroup C conjugate vaccines in the UK, there has been a decrease in the incidence of serogroup C disease, and serogroup B is therefore even more predominant.…”
mentioning
confidence: 99%